2013
DOI: 10.1002/biof.1092
|View full text |Cite
|
Sign up to set email alerts
|

Novel cell‐based assay reveals associations of circulating serum AhR‐ligands with metabolic syndrome and mitochondrial dysfunction

Abstract: Serum concentrations of environmental pollutants have been positively correlated with diabetes and metabolic syndrome in epidemiologic studies. In turn, abnormal mitochondrial function has been associated with the diseases. The relationships between these variables, however, have not been studied. We developed novel cell-based aryl hydrocarbon receptor (AhR) agonist bioassay system without solvent extraction process and analyzed whether low-dose circulating AhR ligands in human serum are associated with parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 40 publications
3
74
0
Order By: Relevance
“…There are several possible mechanisms to link serum AHRT activity and diabetic nephropathy. We have found that serum AHRT activity correlated with its inhibitory function on cell respiration. In the previous report, we showed that serum AHRT activities had a positive correlation with ROS production and a negative correlation with adenosine triphosphate (ATP) levels.…”
Section: Discussionmentioning
confidence: 90%
“…There are several possible mechanisms to link serum AHRT activity and diabetic nephropathy. We have found that serum AHRT activity correlated with its inhibitory function on cell respiration. In the previous report, we showed that serum AHRT activities had a positive correlation with ROS production and a negative correlation with adenosine triphosphate (ATP) levels.…”
Section: Discussionmentioning
confidence: 90%
“…We took such "bottom up" approach and tested if subjects with T2DM or metabolic syndrome have higher serum AhR transactivation activity [69]. We developed novel cell-based AhR ligand activity (CALA) assay without solvent extraction process and analyzed whether low-dose circulating AhR ligands in human serum are associated with parameters of metabolic syndrome and mitochondrial function.…”
Section: Biologic Tests For Edcsmentioning
confidence: 99%
“…When mitochondrial function is perturbed, diseases involving energy utilization easily result: obesity and insulin resistance are prototypes of these diseases [190]. Furthermore, mitochondrial abnormalities are associated with intracellular lipid accumulation, insulin resistance and the pathophysiology of type 2 diabetes [187,191193]. …”
Section: Mechanisms Of Dioxin-induced Beta Cell Dysfunctionmentioning
confidence: 99%